The role of adenosine A2A receptors on neuromuscular transmission upon ageing - Pousinha, Paula Isabel Antunes, 1978- (2012)
Tese de doutoramento, Ciências Biomédicas (Neurociências), Universidade de Lisboa, Faculdade de Medicina, 2012